Respuesta :

Answer: y = -2x+6

slope = -2

y intercept = 6

=====================================================

Explanation:

Let's find the slope

m = (y2-y1)/(x2-x1)

m = (2-4)/(2-1)

m = -2/1

m = -2

The slope is -2

Let's use this slope along with the first point to get the y intercept

y = mx+b

y = -2x+b ... plug in the slope we found earlier

4 = -2*1+b ... plug in the coordinates of the point (1,4)

4 = -2+b

4+2 = -2+b+2 .... adding 2 to both sides

6 = b

b = 6

The y intercept is 6

The equation y = mx+b turns into y = -2x+6 since m = -2 is the slope and b = 6 is the y intercept.

ACCESS MORE